On the politics of the public spaces: public sphere and urban politics in the case of the ecolimite of Rocinha - Machado, Ana Brasil (Geografares, 2018)
The ecolimites project was conceived and implemented throughout the years 2000 in the city of Rio de Janeiro. Its overt goal was to contain the expansion of favelas over areas of environmental protection. In a particular geographical situation, the favela of Rocinha, the project took the form of an urban park equipped with various leisure facilities. This article aims to discuss the implementation of the Rocinha Ecological Park from the perspectives of the public sphere and urban politics, thus contributing to the debate about the political dimension of public spaces.Keywords: ecolimits, public sphere, urban politics.